Scleroderma, primary biliary cirrhosis, and Sjögren's syndrome after cosmetic breast augmentation with silicone injection: a case report of possible human adjuvant disease. Issue 3 (June 1984) - Okano, Y; Nishikai, M; Sato, A
Abstract : A 52-year-old woman developed scleroderma, primary biliary cirrhosis, and Sjögren's syndrome after cosmetic silicone injections. These conditions may possibly represent 'human adjuvant disease'.